Exploring the pseudo-ductility of aligned hybrid discontinuous composites using controlled fibre-type arrangements - Finley,JM; Yu,H; Longana,ML; Pimenta,S; Shaffer,MSP; Potter,KD (Composites Part A: Applied Science and Manufacturing, 2017)
Pseudo-ductility presents a potential means for preventing catastrophic failure in composite materials; large deformations will prevent brittle fracture and provide warning before final failure. This work explores how the pseudo-ductility and strength of aligned hybrid discontinuous composites can be controlled by manipulating the arrangement of different fibre types. Aligned carbon/glass hybrid specimens with different fibre arrangements are manufactured and tested using a modification to the High Performance Discontinuous Fibre (HiPerDiF) method. Experimental results are complemented by an improved virtual testing framework, which accurately captures the fracture behaviour of a range of hybrid discontinuous composite microstructures. With a randomly intermingled fibre arrangement as a baseline, a 27% increase in strength and a 44% increase in pseudo-ductility can be achieved when low elongation fibres are completely isolated from one-another. Results demonstrate that the HiPerDiF method is the current state-of-the-art for maximising the degree of intermingling and hence the pseudo-ductility of hybrid composites.